Case for diagnosis. Eyelid edema and erythematous papules disseminated on the face, - Ana Cristina M. Garcia; Ângela Marques Barbosa; Marilda Aparecida Milanez Morgado de Abreu; Carlos Zelandi Filho (Sociedade Brasileira de Dermatologia, 2020)
Abstract Lupus miliaris disseminatus faciei or acne agminata is a chronic inflammatory disorder of the skin, considered an intriguing entity due to its pathogenesis, which is still largely speculative. It has been linked to tuberculosis, sarcoidosis, rosacea, and other granulomatous diseases, but it is considered an independent entity.